2018
DOI: 10.1159/000489145
|View full text |Cite
|
Sign up to set email alerts
|

Urate-Lowering Agents in Asymptomatic Hyperuricemia: Role of Urine Sediment Analysis and Musculoskeletal Ultrasound

Abstract: Current urate-lowering therapy (ULT) includes three direct acting drugs (allopurinol, febuxostat, Rasburicase) and at least four ‘indirect’ drugs with other important targets (canagliflozin, losartan, fenofibrate and sevelamer). Moreover, the alcalinization of urines using bicarbonate can be used to dissolve urate crystals and the clinician may discontinue several drugs are known to increase serum levels of uric acid, such as diuretics, aspirin, cyclosporine, theophylline, mycophenolate and ACE inhibitors. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…This result raises the possibility that febuxostat was effective for attenuating earlier progression of carotid atherosclerosis, suggesting a limited role of febuxostat on the development of atherosclerosis. Further research is therefore warranted to determine the optimal patients with asymptomatic hyperuricemia who could potentially obtain cardiovascular and renal benefits from treatment with febuxostat [30].…”
Section: Plos Medicinementioning
confidence: 99%
“…This result raises the possibility that febuxostat was effective for attenuating earlier progression of carotid atherosclerosis, suggesting a limited role of febuxostat on the development of atherosclerosis. Further research is therefore warranted to determine the optimal patients with asymptomatic hyperuricemia who could potentially obtain cardiovascular and renal benefits from treatment with febuxostat [30].…”
Section: Plos Medicinementioning
confidence: 99%
“…Another option for treating hyperuricemia is the use of medications with secondary SUA lowering capabilities such as losartan, atorvastatin, calcium channel blockers, sodium-glucose co-transporter 2 (SGLT-2) inhibitors, fenofibrate, sevelamer, metformin, and angiotensin-II/ neprilysin inhibitors (ARNI). Some medications that should be considered for discontinuation because of their known effect to raise SUA are acetylsalicylic acid, cyclosporine, theophylline, mycophenolate, beta-and alpha-1-adrenergic antagonists, and angiotensin-converting enzyme (ACE) inhibitors [5,15,[41][42][43][44].…”
Section: Existent Therapy Modificationmentioning
confidence: 99%
“…The tubular atrophy/interstitial fibrosis caused by SUA might be explained by the following mechanisms. Urate crystals deposit in the renal tubules can directly damage or block the renal tubules, and also form uric acid renal stones to damage the kidney, which results in renal tubular atrophy and interstitial fibrosis, even renal failure (Viggiano et al, 2018). HUA could also promote the production of inflammatory factors such as MCP-1 and TNF-β1, which stimulates the inflammatory response and induce renal tubular injury and renal interstitial fibrosis (Romi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the level of uric acid can predict the incidence of atherosclerosis (Feig, 2014;Gustafsson & Unwin, 2013;Li et al, 2014), hypertension (Wang et al, 2014), and coronary heart disease (Kim et al, 2010;Braga et al, 2016). Moreover, some studies have emphasized that high levels of serum uric acid (SUA) would form urates crystals that deposit in renal tubules and interstitial, leading to kidney fibrosis and failure (Su et al, 2020;Viggiano et al, 2018). Recently, some studies have found that there is a correlation between the SUA level and the progression of IgAN.…”
Section: Introductionmentioning
confidence: 99%